The Role of SHI/STY/SRS Genes in Organ Growth and Carpel Development Is Conserved in the Distant Eudicot Species Arabidopsis thaliana and Nicotiana benthamiana - Gomariz-Fernández, Africa; Sánchez-Gerschon, Verónica; Fourquin, Chloé; Ferrándiz, Cristina (Frontiers in Plant Science, 2017)
Carpels are a distinctive feature of angiosperms, the ovule-bearing female reproductive organs that endow them with multiple selective advantages likely linked to the evolutionary success of flowering plants. Gene regulatory networks directing the development of carpel specialized tissues and patterning have been proposed based on genetic and molecular studies carried out in Arabidopsis thaliana. However, studies on the conservation/diversification of the elements and the topology of this network are still scarce. In this work, we have studied the functional conservation of transcription factors belonging to the SHI/STY/SRS family in two distant species within the eudicots, Eschscholzia californica and Nicotiana benthamiana. We have found that the expression patterns of EcSRS-L and NbSRS-L genes during flower development are similar to each other and to those reported for Arabidopsis SHI/STY/SRS genes. We have also characterized the phenotypic effects of NbSRS-L gene inactivation and overexpression in Nicotiana. Our results support the widely conserved role of SHI/STY/SRS genes at the top of the regulatory network directing style and stigma development, specialized tissues specific to the angiosperm carpels, at least within core eudicots, providing new insights on the possible evolutionary origin of the carpels.